2015
DOI: 10.1016/j.exphem.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

RN-1, a potent and selective lysine-specific demethylase 1 inhibitor, increases γ-globin expression, F reticulocytes, and F cells in a sickle cell disease mouse model

Abstract: Increased levels of fetal hemoglobin are associated with decreased symptoms and increased lifespan in patients with sickle cell disease (SCD). Hydroxyurea, the only drug currently approved for SCD, is not effective in a large fraction of patients, and therefore, new agents are urgently needed. Recently it was found that lysine demethylase 1, an enzyme that removes monomethyl and dimethyl residues from the lysine 4 residue of histone H3, is a repressor of γ-globin gene expression. In this article, we have compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
1
33
0
Order By: Relevance
“…31 Two recent studies have shown that RN-1, a more potent and specific LSD-1 inhibitor than TCP, induced γ-globin expression in human and baboon erythroid progenitors and a sickle cell mouse model. 32,33 In this study we have tested the effect of RN-1 in baboons and confirm that it is a highly potent in vivo inducer of HbF synthesis.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…31 Two recent studies have shown that RN-1, a more potent and specific LSD-1 inhibitor than TCP, induced γ-globin expression in human and baboon erythroid progenitors and a sickle cell mouse model. 32,33 In this study we have tested the effect of RN-1 in baboons and confirm that it is a highly potent in vivo inducer of HbF synthesis.…”
mentioning
confidence: 59%
“…The results confirm and extend our previous studies in the sickle cell mouse model showing that RN-1 increased F cells, F reticulocytes, and γ-globin mRNA to levels similar to decitabine, the most potent HbF-inducer known. 32,33 However, both these drugs elicit only small increases of γ-globin expression in the SCD mouse model compared to the magnitude observed in baboons, emphasizing the importance of using nonhuman primate, such as baboons, to test the effect of HbFinducing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we show that RBCs with mitochondria are associated with high levels of ROS accumulation. Finally, we demonstrate that two preclinical candidate drugs, the LSD1 inhibitor, RN-1(12, 13) and mTOR inhibitor(14), Sirolimus, both reduce levels of mitochondria retaining RBCs in a SCD mouse model.…”
Section: Introductionmentioning
confidence: 85%
“…injection to homozygous SCD mice five days a week for 2 to 4 weeks as previously described (12). For mTOR inhibition, Sirolimus (Rapamycin-Selleck chemicals) was given at a dose of 5mg/kg by intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Although the baboon closely reiterates the structure and switching of the human β-globin locus, the inherent complexities of primate research have limited the number of such studies. Nevertheless, valuable insights have been gained, particularly in preclinical testing of novel therapeutic inducers 8486…”
Section: Animal Models To Manipulate Globin Switchingmentioning
confidence: 99%